Determinants of capital structure of bank: top four largest bank in Malaysia / Norhaireen Aman - Aman, Norhaireen (Faculty of Business Management, 2017)
This research is purposely to know that the impact of capital structure in banking sector is focusing on four largest banks in Malaysia which is Maybank, Public Bank, CIMB and RHB Bank from year 2005 to 2015 (quarterly). Data gathered are from secondary data such as journal and others research paper. The strength of capital shows how well the bank performance is it supports bank daily operations and when anyunexpected problemsoccur. To measure the performance I am using size, profitability, liquidity, asset tangibility and growth in assets. This research is also to knowing which of these independent variables most likely effect capital structures. This as a guideline to solve problem regarding of capital structure in banking sector in the near future. Statistical method use is multiple regressions (panel data) in Malaysia.